Pengaruh Kepemimpinan Transformasional, Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Pegawai Kementerian Pemberdayaan Perempuan dan Perlindungan Anak RI - Friosa, Yudith Restia (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This riset were to determine effect of transformational leadership on organizational culture within the Ministry of Women Empowerment and Child Protection (Kemen PPPA), to determine the impact of leadership one job satisfied within Kemen PPPA, to determine the impact of transformational leadership on performances appprisal within Kemen PPPA, knowing the influence of organization culture on job satisfaction within Kemen PPPA, purposive the influence of organizational culture on performance within Kemen PPPA then knowing the impact of job satisfaction to performance within Kemen PPPA. The research is included the explanatory research, measurements in this study were carried out by testing primary data, data analysis in this research used SEM-PLS technique to analyzed latent variables, indicator variables, comparisons between dependent variables. The relationship between the variables of transformational leadership, organizational culture, job satisfaction and performance shows a positive and significant.